A new canthariphilous species of the genus Atrichopogon Kieffer, 1906 from central Italy (Diptera: Ceratopogonidae). Issue 1 (31st December 2022) - Szadziewski, R.; Gwizdalska-Kentzer, M.; Bologna, M. A.; Molfini, M.
Abstract: The new species Atrichopogon ( Atrichopogon ) tolfensis n. sp . from Tolfa Mountains (Italy, Latium, and Rome) is described and illustrated. Both sexes of the species were collected using cantharidin-baited traps from June 2020 to January 2021. The new species is an atypical member of the genus Atrichopogon .https://urn:lsid:zoobank.org:pub:3A012331-57D7-4532-B3F9-FDEE7C988FFD